2012
DOI: 10.1093/neuonc/nos116
|View full text |Cite
|
Sign up to set email alerts
|

The molecular profile of microglia under the influence of glioma

Abstract: Microglia, which contribute substantially to the tumor mass of glioblastoma, have been shown to play an important role in glioma growth and invasion. While a large number of experimental studies on functional attributes of microglia in glioma provide evidence for their tumor-supporting roles, there also exist hints in support of their anti-tumor properties. Microglial activities during glioma progression seem multifaceted. They have been attributed to the receptors expressed on the microglia surface, to glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
365
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(383 citation statements)
references
References 262 publications
13
365
1
2
Order By: Relevance
“…8 For example, analysis of TAMs in a murine glioma model has reported the acquisition of the alternative, pro-tumor phenotype of TAMs in the course of tumor development. 11 Moreover, a study has shown that a 48-hour incubation with glioma cells triggered an alternative, tumor-promoting profile in human monocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 For example, analysis of TAMs in a murine glioma model has reported the acquisition of the alternative, pro-tumor phenotype of TAMs in the course of tumor development. 11 Moreover, a study has shown that a 48-hour incubation with glioma cells triggered an alternative, tumor-promoting profile in human monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of surgically resected glioblastoma tissues show that as much as 30% of the tissue consisted of tumorassociated microglia/macrophages (TAMs), 5,6 which are derived from parenchymal microglia in the brain and monocytes-derived macrophages from the blood. 7,8 These analyses moreover show that the number of TAMs in the tumor region correlated with the histological grade of gliomas. 9,10 TAMs in the presence of glioma cells become immunosuppressive and elicit an anti-inflammatory response by increasing the expression and release of cytokines such as IL-10 and VEGF, thereby contributing to a milieu that promotes the survival and growth of the glioblastoma cells.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Since then, numerous studies have shown that microglia are found in high-grade malignant gliomas and form the major components of glioma-infiltrating cells [8]. Some studies have indicated that microglia play an immune defensive effect against glioma and inhibit the proliferation and growth of glioma [25].…”
Section: Discussionmentioning
confidence: 99%
“…the issue of whether microglia suppress or enhance glioma growth remains controversial. Compelling evidence has shown that glioma cells could suppress the immune surveillance functions of microglia [8,9] and respond to their products by increasing proliferation or invasion [10]. There also exist hints in support of gliomacytotoxic effects of microglia [11,12].…”
Section: Introductionmentioning
confidence: 99%